Changing perceptions of general health in the Kayseri Province, Turkey in 2004 and 2017: A population-based study - Senol, Vesile; Elmali, Ferhan; Cetinkaya, Fevziye; Nacar, Melis (Frontiers in Public Health, 2023)
Aim Self-rated health (SRH) and health-related quality of life (HRQoL) have closely related outcomes in measuring general health status in community-based studies. The aim of this study is to determine changes in the self-perceived overall health of people and affected factors by comparing the findings of two studies conducted in the same research area. Methods Both studies were conducted using the same measurement tools in households determined by random sampling techniques in the same research areas. The first and second studies were conducted with 1,304 and 1,533 people residing in 501 and 801 households in 2004 and 2017, respectively. The demographic data form, the Nottingham Health Profile (NHP), and a single-item SRH questionnaire were used for data collection. Results The rate of good SRH increased from 56% to 70% while the average NHP score decreased from 30.87 to 20.34. The predictors of negative health perceptions were the presence of chronic diseases (OR 3.4–2.7-times higher), being female (OR.1.4–1.5 times higher), and the completion of primary education only (OR. 2.7–2.8 times higher) both 2004 and 2017. Living 500–1,000 m from the nearest healthcare facility was the main protective variable against poor SRH. Conclusions Good SRH and HRQoL have increased significantly over time. Chronic diseases, education, and gender are the strongest predictors of poor SRH.